Identification of a DNA transformation gene required for com101A+ expression and supertransformer phenotype in Haemophilus influenzae. - Zulty, J J (1995)
DNA sequencing, RNA mapping, and protein expression experiments revealed the presence of a gene, tfoX+, encoding a 24.9-kDa polypeptide, that is transcribed divergently from a common promoter region with the Haemophilus influenzae rec-1+ gene. H. influenzae strains mutant for tfoX failed to bind transforming DNA and were transformation deficient. Primer extension experiments utilizing in vivo total RNA from precompetent and competent H. influenzae cells demonstrated that transcription of tfoX+ increased immediately upon competence induction, suggesting that tfoX+ is an early competence gene. Similar experiments showed that the expression of the late competence-specific gene, com101A+, was tfoX+ dependent. Moreover, expression of plasmid-borne tfoX+ in H. influenzae resulted in constitutive competence. The addition of cyclic adenosine monophosphate (cAMP) to strains carrying a tfoX::lacZ operon fusion resulted in an immediate increase in beta-galactosidase activity that correlated with an increase in genetic transformability. Collectively, our results suggest that TfoX may play a key role in the development of genetic competence by regulating the expression of late competence-specific genes.